In Vivo Study of Nasal Bone Reconstruction with Collagen, Elastin and ChitosanMembranes in Abstainer and Alcoholic Rats - Pandini, Fabricio Egidio; Miyauchi Kubo, Fabíola Mayumi; De Guzzi Plepis, Ana Maria; Da Conceição Amaro Martins, Virginia; Da Cunha, Marcelo Rodrigues; Silva, Vinicius Rodrigues; Hirota, Vinicius Barroso; Lopes, Everton; Menezes, Marcos Antonio; Pelegrine, André Antonio; De Andrade, Tiago Negrão; Iatecola, Amilton; et al. (MDPI, 2022)
The aim of the present study was to evaluate the use of collagen, elastin, or chitosan biomaterial for bone reconstruction in rats submitted or not to experimental alcoholism. Wistar male rats were divided into eight groups, submitted to chronic alcohol ingestion (G5 to G8) or not (G1 to G4). Nasal bone defects were filled with clot in animals of G1 and G5 and with collagen, elastin, and chitosan grafts in G2/G6, G3/G7, and G4/G8, respectively. Six weeks after, all specimens underwent radiographic, tomographic, and microscopic evaluations. Bone mineral density was lower in the defect area in alcoholic animals compared to the abstainer animals. Bone neoformation was greater in the abstainer groups receiving the elastin membrane and in abstainer and alcoholic rats receiving the chitosan membrane (15.78 ± 1.19, 27.81 ± 0.91, 47.29 ± 0.97, 42.69 ± 1.52, 13.81 ± 1.60, 18.59 ± 1.37, 16.54 ± 0.89, and 37.06 ± 1.17 in G1 to G8, respectively). In conclusion, osteogenesis and bone density were more expressive after the application of the elastin matrix in abstainer animals and of the chitosan matrix in both abstainer and alcoholic animals. Chronic alcohol ingestion resulted in lower bone formation and greater formation of fibrous connective tissue.
Keywords: Alcohol intake; Bone regeneration; Bone repair; Chitosan; Collagen; Elastin; Scaffolds